(3TQM GdTGWHjIs - (3eLghds
(3ChdgG (B:s
.. (3hbGdhf YjSi Ke YKeGf hQTge HUMHJg GdeLO GdQajY JCKdG , U jPcQ GKfjf ef CUMGHg haGA HhYOg hjbhd bGdhf gh GdeSei HYjSi (B...s
(3BNQgG (B:s
... (3aGHOC efgG HGdeNGQL eQOaG dgG GdUaGJ eaUdG H GdeNGQL LeY eNQL (B.. (3BNQ GdeaUd GdeHjf M GdgGA aj efgG GeG ddMQha eVGa Cj ef CMcGe GdMQha (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs